I'mRT MatriXX Array Characterization And Spatial Modification Simulations In Intensity Modulated Radiation Theraphy (IMRT) At 6 MV Photon Beam In Nasopharynx Cancer - alAshrah, Saleh Abdullah (2011)
Two types of 2D pixel ionization chambers: I’mRT MatriXX from Scanditronix- Wellhöfer in Mount Mariam Hospital and Seven29TM from PTW‐Freiburg in King Faisal special Hospital and Research Center (KFSH&RC) in Riyadh were studied with the objective to implement for quality assurance in IMRT treatment plan verification. The effective point measurement of the I’mRT MatriXX and Seven29TM were verified and it agreed with the manual specifications. The reproducibility of the I’mRT MatriXX detector was tested for the short-, medium- and long-term.